Coordinated distributed adaptive perimeter control for large-scale urban road networks. (April 2017) - Haddad, Jack; Mirkin, Boris
Highlights: Developing interconnected general form of R-region MFDs model. Introducing a coordinated distributed adaptive perimeter (DAP) control scheme. Designing DAP controllers according to model reference adaptive control theory with coordination. Compensating uncertainty of model parameters and unknown bounded external disturbances. Proving stability and exact asymptotic tracking for DAP control laws. Abstract: Perimeter traffic control for large-scale urban road networks has been studied by several researchers during the last decade. Recently, the initial steps towards taking into account model's uncertainties under control synthesis were made in Haddad and Shraiber (2014) and Haddad (2015), where by considering one- and multi- region control problem, respectively, a robust perimeter control has been designed to systematically take into account uncertainties in MFD-based dynamics, e.g. the MFD scatter. The robust control design can provide a fixed controller with constant gains to compensate all uncertainties, following the worst case scenario concept. In this paper, an adaptive control scheme is developed. Similarly to robust control, the developed adaptive control scheme postulates one controller structure, however, the controllers' gains vary with time to adapt themselves against the model parameter uncertainties. In this paper, in order to accommodate uncertainties and take into consideration the restrictions on the available information, we deal with the adaptive perimeter control problem for multi-region MFD systems, which have an interconnected structure composing several homogeneous regions. Unlike previous works that assume centralized approach, where feedback informations are needed from all urban regions, in this paper we follow a coordinated distributed control approach, where regional control laws are developed depending on (i) real on-line local information of the region, i.e. regional accumulation and its perimeter control input only, and (ii) reference signal information forwarded to all distributed perimeter controllers by a high level coordinator controller.